Perancangan Aplikasi Sistem Pendaftaran Rekam Medis Rawat Jalan di Bidan Praktik Mandiri Sri Sayekti Kebumen Berbasis Web - Dani Prasetyo; Bangkit Ary Pratama (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Registration of medical records in outpatients in BPM Sri Sayekti Kebumen still used paper so as to cause problems such as difficulty in finding data so it takes a long time, document storage was still not good because some sheets of paper stored side by side with various other documents so that when reporting data loss or missfile, and often the occurrence of double data, due to negligence in storing documents and the risk of mixing with other documents. The purpose of the research was to design a web-based outpatient medical record registration application program. The type of research used is descriptive. The methods used were observation and interview. Data collection was used a cross sectional approach. The results of the study at BPM Sri Sayekti Kebumen in out patient registration serviced still use a manual system that uses paper media. As for the daily census reporting outpatients are still done manually through the register book of outpatients. The conclusion of this study was one way to solve the problems in BPM Sri Sayekti Kebumen, especially the installation of registration, namely the design of an application program for web-based outpatient medical record registration system.